The value of dementia care towards the end of life—A contingent valuation study. (24th January 2020) - Bhattarai, Nawaraj; Mason, Helen; Kernohan, Ashleigh; Poole, Marie; Bamford, Claire; Robinson, Louise; Vale, Luke
Abstract : Objectives: A dementia nurse specialist (DNS) is expected to improve the quality of care and support to people with dementia nearing, and at, the end of life (EoL) by facilitating some key features of care. The aim of this study was to estimate willingness‐to‐pay (WTP) values from the general public perspective, for the different levels of support that the DNS can provide. Methods: Contingent valuation methods were used to elicit the maximum WTP for scenarios describing different types of support provided by the DNS for EoL care in dementia. In a general population online survey, 1002 participants aged 18 years or more sampled from the United Kingdom provided valuations. Five scenarios were valued with mean WTP value calculated for each scenario along with the relationship between mean WTP and participant characteristics. Results: The mean WTP varied across scenarios with higher values for the scenarios offering more features. Participants with some experience of dementia were willing to pay more compared with those with no experience. WTP values were higher for high‐income groups compared with the lowest income level ( P  < .05). There was no evidence to suggest that respondent characteristics such as age, gender, family size, health utility or education status influenced the WTP values. Conclusion: The general population values the anticipated improvement in dementia care provided by a DNS. This study will help inform judgements on interventions to improve the quality of EoL care.